MiR‐146a Deletion Protects From Bone Loss in OVX Mice by Suppressing RANKL/OPG and M‐CSF in Bone Microenvironment. (4th September 2019) - Zhao, Jingyu; Huang, Mingjian; Zhang, Xudong; Xu, Jiajia; Hu, Guoli; Zhao, Xiaoying; Cui, Penglei; Zhang, Xiaoling
ABSTRACT: MicroRNAs play important roles in osteoporosis and show great potential for diagnosis and therapy of osteoporosis. Previous studies have demonstrated that miR‐146a affects osteoblast (OB) and osteoclast (OC) formation. However, these findings have yet to be identified in vivo, and it is unclear whether miR‐146a is related to postmenopausal osteoporosis. Here, we demonstrated that miR‐146a knockout protects bone loss in mouse model of estrogen‐deficient osteoporosis, and miR‐146a inhibits OB and OC activities in vitro and in vivo. MiR‐146a −/− mice displayed the same bone mass as the wild type (WT) but exhibited a stronger bone turnover than the WT did under normal conditions. Nevertheless, miR‐146a −/− mice showed an increase in bone mass after undergoing ovariectomy (OVX) compared with those subjected to sham operation. OC activities were impaired in the miR‐146a −/− mice exposed to estrogen deficiency, which was diametrically opposite to the enhanced bone resorption ability of WT. Macrophage colony‐stimulating factor (M‐CSF) and receptor activator of NF‐κB ligand (RANKL)/osteoprotegerin (OPG) from a bone microenvironment affect this extraordinary phenomenon. Therefore, our results implicate that miR‐146a plays a key role in estrogen deficiency–induced osteoporosis, and the inhibition of this molecule provides skeleton protection. © 2019 American Society for Bone and Mineral Research.